The Testimony of Jesus Revelation 12:17 - Leonard Valwen Tan (Fakultas Filsafat Universitas Advent Indonesia, 2026)
This study examines the biblical and theological meaning of “the testimony of Jesus” in Revelation 12:17 within Seventh-day Adventist theology. Through exegetical analysis of the Greek phrase martyria Iēsou, it explores its interpretation in light of Revelation 19:10, which identifies the testimony of Jesus as “the spirit of prophecy.” The study situates this concept within the broader themes of covenant faithfulness, justification by faith, and the Great Controversy. It argues that the testimony of Jesus represents prophetic revelation originating from Christ and functioning to preserve doctrinal truth, strengthen believers, and guide the end-time remnant. Consistent with the Protestant principle of sola Scriptura, the prophetic gift is understood as subordinate to and centered on Scripture. Within this framework, the ministry of Ellen G. White is viewed as a historical manifestation of the biblical gift of prophecy. The study concludes that the testimony of Jesus reinforces the authority of Scripture, affirms justification by faith, and supports a Christ-centered eschatological identity.